A prospective comparison of breast sensibility after reduction mammoplasty: Superior versus superomedial pedicle. Issue 12 (December 2019) - Silhol, Thomas; Chaouat, Marc; Harizi, Rafik; Lambert, Jérôme; Noel, Warren; Mimoun, Maurice; Boccara, David
Summary: Background: Breast sensitivity is a significant issue in preoperative consultation prior to reduction mammoplasty. Although a range of techniques is used, recovery of sensation is usually evaluated using the inferior pedicle. Our objective was to evaluate and compare the change in breast sensitivity using the superomedial versus the superior pedicle. Methods: We performed a non-randomized, monocentric, prospective study. Thirty-six patients were examined by a single evaluator with von Frey monofilaments on the day prior to the surgery, at 3–6 months, and at 1 year postoperatively. The breast skin, areola, and nipple sensitivity were tested. The breasts were classified into two groups depending on whether the superior pedicle (S) or the superomedial pedicle (SM) technique was used. Results: The differences between the two groups indicate that the SM group had better sensitivity at 4.5 and 12 months postoperatively. The thresholds for the size filaments that could be felt at the first follow-up on the skin, the areola, and the nipple for the S group vs. the SM group were 2.55 vs. 2.41 ( p  = 0.41), 4.57 vs. 4.45 ( p  = 0.28), and 4.17 vs. 3.81 ( p  = 0.04) size units, respectively. At 1 year postoperatively, the respective values were 2.62 vs. 2.52 ( p  = 0.49), 4.28 vs. 4.05 ( p  = 0.04), and 3.63 vs. 3.38 ( p  = 0.10). Conclusion: The nerve fibers appear to be better preserved in the superomedial pedicle than in the superior pedicle. However, these differences were not clinically relevant. The choice of the technique should be made on the basis of the size and the shape of the breast, the patient morphology, and the operator's preference rather than being on the basis of the recovery of sensitivity.